The Effect Of Picture Stories On The Recall Memory Ability Of Elementary School Students - Fitriyani Fitriyani; Asep Supena (Universitas PGRI Adi Buana Surabaya, 2023)
This study aimed to determine the effect of picture stories on the recall memory ability of elementary school students. This study's population and sample were all SD X's fourth-grade students, totaling 36 students. This quasi-experimental research compares two groups of research targets, one treatment group (experimental) and one control group. The research design used in this study was a